Association between cholecystectomy/gallbladder pathology and colorectal polyps: a systematic review and meta-analysis - Li, Shirui; Deng, Yunfan; Dai, Sheng; Fan, Qi; Xiong, Dehai; Li, Xiuyang (Frontiers in Oncology, 2026)
BackgroundGallbladder-related pathologies may influence colorectal carcinogenesis, yet systematic evaluation of their associations with precursor lesions remains limited. This study addresses critical knowledge gaps by investigating the dual-axis relationship between cholecystectomy/gallbladder pathologies and colorectal polyp risk while elucidating geographical and biological effect modifiers.MethodsIn accordance with the MOOSE/Cochrane guidelines, 27 observational studies were analysed through PROSPERO (CRD420251012876). Comprehensive meta-analysis was performed to assess the effects of cholecystectomy across polyp subtypes and gallbladder pathology (stones/polyps) associations. Heterogeneity was quantified via I² statistics, and pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated via the DerSimonian–Laird random effects model to account for between-study variance. Subgroup analysis stratified by geography, pathology type, and adjustment model was performed with χ² tests for subgroup differences. Sensitivity analysis and publication bias were assessed through leave-one-out methods, funnel plots and Egger’s test.ResultsCholecystectomy was associated with a 39% increased risk (OR = 1.39, 95% CI: 1.21–1.59), with East Asian populations exhibiting a nearly doubled risk compared with North American populations (OR=1.95(95%CI:1.44-2.63) vs OR=1.16(95%CI:1.00-1.34). Compared with unclassified polyps, adenomas were more strongly associated (OR = 1.37, 95% CI: 1.16–1.62). Medium-sized studies (OR = 1.69, 95% CI: 1.36–2.11) and those adjusted for health factors (OR = 1.34, 95% CI: 1.12–1.61) yielded higher estimates, whereas dietary adjustment nullified significance. Gallbladder pathology (stones/polyps) conferred a 27% higher risk overall, with gallbladder polyps showing greater risk (OR = 1.30, 95% CI: 1.17–1.38) than stones (OR = 1.20, 95% CI: 1.08–1.32). Older populations (≥50 years) had stronger associations OR=1.41(95%CI:1.20-1.66) vs OR=1.20(95%CI:1.10-1.30). Adjustment for smoking, alcohol, and BMI strengthened the estimates (OR = 1.43, 95% CI: 1.22–1.68). Sensitivity analysis supported the robustness of the primary findings, particularly for cholecystectomy.ConclusionsThis comprehensive analysis establishes gallbladder status as an independent risk modulator for early colorectal lesions, with cholecystectomy demonstrating the highest risk magnitude. These findings advocate personalized surveillance strategies that integrate gallbladder history, particularly high-risk demographics. The mechanistic synergies between bile acid dysmetabolism and gut microbiota dysbiosis warrant further exploration as preventive targets. Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251012876.